From bullet to bullhorn: stories of advocacy, activism and hope - Schaffer, Lois A. (Red Penguin Books, 2021)
"The purpose of this book is to demonstrate that gun violence has claimed the lives of many innocent people. At any given moment, the easy accessibility of guns results in devastating losses of innocent lives. There are the victims and the victimized, otherwise known as survivors. Contained within these pages is a compilation of stories written by eighteen people located in various states throughout our country - some who were personally affected by gun violence, others who were not. The others included are professionals whose lives were indirectly affected who voiced their unequivocal cry to eliminate the easy accessibility of guns that resulted in senseless deaths. These include people from many walks of life and different states, whose only common connection is the loss of life due to the gun and gun violence. Those who were personally affected may be considered victims, but they refuse to be victimized. Rather, they consider themselves to be survivors. The victims were those who were lost, loved ones, whose lives were suddenly and senselessly cut short. These are their stories. They are all true stories written about and by people from various parts of our country whose lives were impacted and changed forever due to the accessibility of guns."--amazon